2021
DOI: 10.1063/5.0070773
|View full text |Cite
|
Sign up to set email alerts
|

Domain wall pinning through nanoscale interfacial Dzyaloshinskii–Moriya interaction

Abstract: Neuromorphic computing (NC) has been gaining attention as a potential candidate for artificial intelligence. The building blocks for NC are neurons and synapses. Research studies have indicated that domain wall (DW) devices are one of the most energy-efficient contenders for realizing NC. Moreover, synaptic functions can be achieved by obtaining multi-resistance states in DW devices. However, in DW devices with no artificial pinning, it is difficult to control the DW position, and hence achieving multilevel re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Subsequently, our group studied the concept of altering the magnetic properties locally to pin the DWs . This was done using the concepts of ( i ) local nonmagnetic metal diffusion at specific positions of a FM wire, ( ii ) implantation of nonmagnetic ions in an FM wire, ( iii ) local change of spin configuration by utilizing the exchange coupling between IP and OOP magnetized (DW device) wire, and ( iv ) introducing i DMI locally at specific centers to pin the DWs. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, our group studied the concept of altering the magnetic properties locally to pin the DWs . This was done using the concepts of ( i ) local nonmagnetic metal diffusion at specific positions of a FM wire, ( ii ) implantation of nonmagnetic ions in an FM wire, ( iii ) local change of spin configuration by utilizing the exchange coupling between IP and OOP magnetized (DW device) wire, and ( iv ) introducing i DMI locally at specific centers to pin the DWs. , …”
Section: Resultsmentioning
confidence: 99%
“…38 This was done using the concepts of (i) local nonmagnetic metal diffusion at specific positions of a FM wire, 93 (ii) implantation of nonmagnetic ions in an FM wire, 94 (iii) local change of spin configuration by utilizing the exchange coupling between IP and OOP magnetized (DW device) wire, and (iv) introducing iDMI locally at specific centers to pin the DWs. 95,96 From the point of view of commercial implementation of NC, geometric pinning appears to be practical. This is because the synapse can be patterned in one lithography step.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve controlled, reliable, and reproducible DW motion, researchers studied different mechanisms to pin the DWs at desired positions. These are termed as artificial pinning sites and can be of geometrical (shape) or nongeometrical (magnetic properties) origin. , Several such pinning sites could be used to achieve intermediate magnetization (multiple resistance) states in DW-MTJ devices. In earlier days of DW device research, artificial pinning sites in the shape of triangular notches were introduced to demonstrate DW pinning.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al demonstrated multiple resistance states by modifying interfacial Dzyaloshinskii–Moriya interaction ( i DMI) locally via micromagnetic simulations. [ 48 ] In another approach, the pinning can be achieved via geometric modulation. [ 43 ] Siddiqui et al demonstrated multiple resistance states in the MTJ device by linearly varying the width of HM.…”
Section: Spintronic Devices For Neuromorphic Applicationsmentioning
confidence: 99%